(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
Purpose of the study of great importance is the rational choice when using non-steroidal antiinflammatory drugs in the treatment of chronic bacterial prostatitis, determining the effectiveness and ensuring its safety.